A Comparative Study on the Spatial Characteristics of Traditional Residential Houses in Zhangguying and Laodong Villages Based on Space Syntax. Issue 3 (May 2021) - Zou, Han; Liu, Yang
Abstract: This article is based on space syntax theoy combined with field surveys and mapping data, Using AutoCad and Depthmap to analyze and interpret the spatial characteristics of traditonal houses in Zhangguying Village and Laodong Village in Xiangxi Prefecture. clarifying the difference in spatial characteristics between the two spaces and the influencing factors behind the difference by comparing the integration degree of visible layer and the degree of integration of the feasible layer.